DUE DILIGENCE IN THE EXECUTION OF OFFICE AND THE LEGAL CONSEQUENCES FOR NOTARIES - Ida Bagus Putra Raharja (Warmadewa Press, 2024)
A notary is the only public official who has the authority to make authentic deeds relating to all creations and legal events desired by the parties or as determined by the applicable law and has the aim that all legal acts and events have the power as perfect evidence. This research aims to discuss the Notary's authority to carry out due diligence in carrying out his office duties and the Notary's responsibility regarding his authority to carry out legal counseling regarding the making of deeds. The research method used in this research is a normative legal research method. Notaries in carrying out Due Diligence apply the precautionary principle with the limitation that if documents or information occur that are incorrect because they are fake or falsified, the Notary is not qualified to violate his/her official duties. The Notary's responsibility regarding his authority to provide legal counseling regarding the making of deeds is stated in Article 15 paragraph (2) of the Law on the Position of Notaries which states that notaries have the authority to provide legal counseling in relation to making deeds. In providing legal counseling in connection with the making of a deed, it means that the Notary has the authority to provide legal counseling in relation to the deed he or she is making.